Using Wormholes to Solve the Problem of Evil - Nikk Effingham (TheoLogica, 2020)
The Multiverse Response to the problem of evil has it that God made our universe because God makes every universe meeting a certain standard. The main problem for that response is that there’s no explanation for why God didn’t just keeping making duplicates of perfect universes. This paper introduces the ‘Multiactualities Response’, which says that God actualises every possible world that meets a certain standard of value. It avoids the corresponding problem about duplication because different propositions must always be true at distinct worlds. The Multiactualities Response nevertheless has its own problem, namely that it requires the possibility of multiple actual worlds. This paper argues that if we consider spacetimes with wormholes, we have good cause to think there can be multiple metaphysically privileged present moments; given a suitable analogy between time and modality, it follows that there can be multiple metaphysically privileged (i.e. actual) worlds. This paper includes an in–depth examination of the metaphysics of both the temporal and modal cases.